Securing Forest Tenure Rights for Rural Development : : Lessons from Six Countries in Latin America - Segura Warnholtz, Gerardo (Washington, DC: PROFOR, 2017)
Secure land tenure in rural landscapes is widely recognized as an essential foundation for achieving a range of economic development goals. However, forest areas in low and middle-income countries face particular challenges in strengthening the security of land and resource tenure. Forest peoples are often among the poorest and most politically marginalized communities in their national contexts, and their tenure systems are often based on customary, collective rights that have insufficient formal legal protection. This study on Securing Forest Tenure Rights for Rural Development aims to contribute to efforts worldwide to reduce poverty and strengthen sustainable management in forest areas. It does so by reviewing the progress of tenure reforms in six countries in Latin America, and drawing lessons to help advance the realization of these reforms and inform similar initiatives in other countries. The target audience of this work includespolicy-makers who have responsibility for forests, climate change, land tenure, agricultural development and poverty reduction programs in rural areas, as well as for civil society organizations and international partners working on land tenure and natural resource governance. The study also aims to assist and inform the work of World Bank programs in rural development, environment and natural resources, agriculture, social development, climate change, and carbon finance, by increasing attention and support to indigenous and community forest tenure as it relates to these areas of work.